Genetic Diversity and Historical Demography of Physalaemus centralis (Anura, Leptodactylidae) in the Cerrado - Amanda Varago (2025)
Understanding the evolutionary history of species is crucial for developing effective conservation strategies, particularly in biodiversity hotspots like the Cerrado. This biome, known for its high endemism, faces increasing threats from habitat loss and climate change. Amphibians, due to their sensitivity to environmental changes and limited dispersal abilities, are especially vulnerable, making them valuable models for studying biodiversity dynamics. The Neotropical frog Physalaemus centralis, endemic to the Cerrado, offers an ideal case to investigate how historical climatic fluctuations, geological events, and ecological barriers have shaped genetic diversity and population structure. Its wide distribution across the Cerrado encompasses diverse ecological conditions and potential barriers, providing a representative model for understanding how environmental heterogeneity influences evolutionary processes. By analyzing the phylogeographic patterns of P. centralis using mitochondrial DNA (16S rRNA) from 66 samples across its range, we identified two distinct genetic groups that diverged approximately 4.99 million years ago during the Miocene-Pliocene transition. These groups exhibit contrasting genetic diversity and geographic distributions, influenced by historical climatic shifts and ecological constraints. The Bayesian Skyline Plot indicated population stability in both groups, while ecological niche models highlighted the role of past climatic changes in shaping habitat connectivity and refugia. These findings underscore the Cerrado’s dual role as both a refuge and a driver of diversification, emphasizing its importance in the evolutionary history of P. centralis. This study provides key insights into the processes driving and maintaining biodiversity in this threatened biome, forming a foundation for targeted conservation efforts to preserve the genetic and ecological resilience of P. centralis and other Cerrado species.